Synergistic modified lithium-rich manganese-based positive electrode material and preparation method and application thereof

The precursor of the lithium-rich manganese-based hydroxide system containing Al was synthesized by co-precipitation method, and the W and B sources were doped during the two sintering processes to form a coordinated modified lithium-rich manganese-based positive electrode material, which solved the problems of low initial charge/discharge capacity of the material, low Coulomb efficiency, poor circulation performance and poor rate performance, and achieved significant performance improvement.

CN119833613APending Publication Date: 2025-04-15BEIJING UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510039909.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Lithium-rich manganese-based cathode materials have problems in terms of low initial charge/discharge capacity, low first-time Coulomb efficiency, poor circulation performance and poor rate performance, which is difficult to meet the needs of industrial production.

Method used

The precursor of lithium-rich manganese-based hydroxide system containing Al was synthesized by co-precipitation method, and the W and B sources were doped respectively during the two sintering processes to form a co-doping of Al and W and a synergistic lithium-rich manganese-based positive electrode material with surface construction oxygen vacancy and spinel structure.

Benefits of technology

The first-time Coulomb efficiency, rate performance and cycle stability of the material are significantly improved, the irreversible capacity is reduced, and the transmission dynamics of Li+ is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236624420000121
    Figure BDA0005236624420000121
  • Figure HDA0005236624520000011
    Figure HDA0005236624520000011
  • Figure HDA0005236624520000012
    Figure HDA0005236624520000012
Patent Text Reader

Abstract

The invention discloses a synergistically modified lithium-rich manganese-based positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of lithium ion battery positive electrode materials. The method specifically comprises the following steps: synthesizing an Al-containing lithium-rich manganese-based hydroxide system precursor by adopting a coprecipitation method, uniformly mixing the Al-containing lithium-rich manganese-based hydroxide system precursor with a lithium source and a W source according to a certain proportion, and sintering in an air atmosphere to obtain an Al and W co-doped lithium-rich manganese-based positive electrode material; and uniformly mixing the obtained positive electrode material and a B source according to a certain mass ratio, carrying out secondary sintering, and naturally cooling to room temperature to obtain the synergistically modified lithium-rich manganese-based positive electrode material. The lithium-rich manganese-based positive electrode material obtained by the method has an Al-doped layered structure in a bulk phase, the W element is pinned in a grain boundary, and the surface has an oxygen vacancy, a fast ion conductor coating and a spinel structure; the electrochemical performance of the modified positive electrode material is obviously improved, and the modified positive electrode material has the advantages of simple preparation method, suitability for large-scale production and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a synergistically modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof, belonging to the technical field of lithium ion battery positive electrode materials. Background Art

[0002] Lithium-ion batteries play an increasingly important role in the utilization of renewable energy due to their advantages such as long life, high energy density and no memory effect. They are considered to be one of the most promising electrochemical energy storage devices and are widely used in energy storage power stations, 3C products, electric vehicles and other fields.

[0003] Lithium-rich manganese-based cathode materials (xLi2MnO3·1-xLiNi a Mn 1-a-b Co b O2,0<x<1,0<a<1,0≤b<1) has a twin domain structure, and Li2MnO3 can be activated at a voltage above 4.4V to provide additional capacity. Low-voltage lithium-rich manganese-based positive electrode materials are prepared by introducing a small amount of Li2MnO3 domain structure into LiTMO2. The introduction of Li2MnO3 can stabilize the structure during charging and discharging in the low voltage range (below 4.4V), and has good cycle stability, making it more suitable as a positive electrode material for energy storage batteries. Carbonate system and hydroxide system are currently the two main systems for preparing precursors for lithium-rich manganese-based positive electrode materials. However, since the solubility product constants of transition metal ions such as Ni, Mn, and Co are close to those of hydroxide, but differ greatly from those of carbonate, this may make it difficult for metal ions to precipitate evenly when preparing carbonate precursors. At the same time, compared with the hydroxide system precursor, the preparation process of the carbonate precursor may require more complex equipment and higher costs, so the hydroxide system has received widespread attention. However, compared with carbonate system precursors, the kinetics of lithium-rich manganese-based cathode materials prepared by hydroxide system precursors are worse and have lower rate performance. In order to improve the above problems, surface treatment, element doping, special morphology and structure design are currently used to modify hydroxide lithium-rich cathode materials.

[0004] For example, patent CN115064682A adds metal nitrate and titanium compounds to anhydrous ethanol to treat the hydroxide system precursor and sinter with lithium to obtain a lithium-rich manganese-based layered oxide with surface and bulk phase co-modification. The treated material has a high discharge specific energy and excellent cycle stability. However, the liquid phase treatment used in this method is prone to produce a large amount of wastewater, which pollutes the environment and is not suitable for actual production and amplification. The anhydrous ethanol used is expensive, and excessive use can easily cause safety problems. For example, patent CN118684271A uses bismuth nitrate, tellurium dioxide and organic ligands to treat the hydroxide system precursor and sinter with lithium to obtain a coated and modified lithium-rich manganese-based positive electrode material, which improves the discharge capacity and cycle performance of the material. However, the drugs used in this method are toxic and expensive, and are still not suitable for industrial and commercial large-scale production and preparation.

[0005] Therefore, in view of the above problems, the present invention proposes a modified lithium-rich manganese-based positive electrode material and a preparation method thereof with simple operation steps and large-scale industrial production, which improves the inherent intrinsic defects of the lithium-rich manganese-based positive electrode such as low initial charge / discharge capacity, low first coulombic efficiency, poor cycle performance and poor rate performance, thereby providing a modification method and use for improving the performance of lithium-rich manganese-based positive electrode materials. Summary of the invention

[0006] The purpose of the present invention is to provide a synergistically modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof, which aims to solve the problems of low first coulombic efficiency, poor rate performance, and poor cycle stability of lithium-rich manganese-based positive electrode materials.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] A co-precipitation method is used to synthesize an Al-containing lithium-rich manganese-based hydroxide system precursor, which is uniformly mixed with a lithium source and a W source in a certain amount and then sintered in an air atmosphere to obtain an Al- and W-co-doped lithium-rich manganese-based positive electrode material; the obtained positive electrode material is uniformly mixed with a B source in a certain mass ratio and secondary sintered, and then naturally cooled to room temperature to obtain a synergistically modified lithium-rich manganese-based positive electrode material.

[0009] The above-mentioned synergistically modified lithium-rich manganese-based positive electrode material and its specific preparation method and application include the following steps:

[0010] (1) mixing a nickel source, a manganese source, a cobalt source and an Al source in deionized water to obtain a transition metal source solution, adding a complexing agent and a precipitant to the transition metal source solution to perform nucleation and growth of particles, and filtering, washing and drying to obtain a lithium-rich manganese-based precursor;

[0011] (2) mixing the lithium-rich manganese-based precursor, the lithium source and the W source in step (1) to obtain a mixture;

[0012] (3) performing a first sintering on the mixture of step (2) to obtain a sintered positive electrode material;

[0013] (4) After mixing the first sintered positive electrode material in step (3) with the B source, a second sintering is performed to obtain the synergistically modified lithium-rich manganese-based positive electrode material.

[0014] The nickel source in step (1) includes any one of nickel sulfate, nickel nitrate or nickel acetate or a combination of at least two thereof, the manganese source includes any one of manganese sulfate, manganese nitrate or manganese acetate or a combination of at least two thereof, the cobalt source includes any one of cobalt sulfate, cobalt nitrate or cobalt acetate or a combination of at least two thereof, the Al source includes any one of aluminum sulfate, aluminum nitrate, aluminum acetate or aluminum oxide or a combination of at least two thereof, the molar ratios of nickel, manganese and cobalt in the nickel source, manganese source and cobalt source are respectively (0.1-0.5):(0.5-0.9):(0-0.5), and the molar sum of nickel, manganese and cobalt is 1; the introduction ratio of the Al source in the transition metal source solution in step (1) is 0.1-50 g / L, and the total concentrations of nickel, manganese and cobalt corresponding to the nickel source, manganese source and cobalt source in the transition metal source solution are 1-4 mol / L.

[0015] The precipitant in step (1) is sodium hydroxide, which is pumped in at a concentration of 1-6 mol / L; the complexing agent in step (1) includes any one of ammonia water, sodium tartrate or citric acid, or a combination of at least two of them, which is pumped in at a concentration of 0.5-10 mol / L.

[0016] In step (1), the particle nucleation and growth process is carried out at a temperature of 30-60° C., a pH value of 9-12, a stirring speed of 600-1400 rpm, and a liquid feeding speed of 20-700 mL / h, so that the particle size D50 of the lithium-rich manganese-based precursor is 2-12 μm.

[0017] The molar ratio of the precursor to the lithium source in step (2) is 1:(0.9-2.0), and the lithium source includes any one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium manganate, lithium sulfide, lithium chloride, lithium sulfate, lithium iodide, lithium bromide or lithium peroxide, or a combination of at least two of them; the mass ratio of the lithium-rich manganese-based precursor to the W source in step (2) is 1:(0.001-0.5), and the W source includes any one of tungsten oxide, sodium tungstate, ammonium tungstate, calcium tungstate, cobalt tungstate, ferrous tungstate or zinc tungstate, or a combination of at least two of them.

[0018] Step (3) The atmosphere of the first sintering is an air atmosphere, and the first sintering includes a first-stage sintering and a second-stage sintering performed in sequence, the heating rate of the first-stage sintering is 1-10°C / min, the first-stage sintering is heated to 150-650°C, and then the insulation time is 0-10h (0 represents direct second-stage sintering without insulation), the heating rate of the second-stage sintering is 1-10°C / min, the second-stage sintering is heated to 650-1100°C, and then the insulation time is 5-24h, and the second-stage sintering is cooled to room temperature after cooling to obtain the first-stage positive electrode material.

[0019] In step (4), the mass ratio of the fired positive electrode material to the B source is 1:(0.001-0.5), and the B source includes any one of boric acid, borate, boron trioxide, cobalt boride or molybdenum boride, or a combination of at least two thereof.

[0020] In step (4), the sintered positive electrode material and the B source are mixed uniformly according to a certain mass ratio, placed in a crucible or a sagger, placed in a sintering furnace, heated to 200°C-800°C at a heating rate of 1-10°C / min and kept warm for 1-12h, and then cooled to room temperature with the furnace to obtain the synergistically modified lithium-rich manganese-based positive electrode material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) High initial coulombic efficiency

[0023] After modification, the irreversible capacity is reduced, the Li+ transfer kinetics are increased, and the first coulombic efficiency of the material is significantly improved.

[0024] (2) Good rate performance

[0025] After modification, W doping makes the primary particles refined, and the oxygen vacancies and spinel phases generated on the surface can promote Li+ transport, and the rate performance is significantly improved.

[0026] (3) Good cycle stability

[0027] After modification, the Al element doped in the bulk phase of the material forms an Al-O bond with stronger bond strength than the TM-O bond, which can bind unstable oxygen and stabilize the structure; the W element segregates at the grain boundary, inhibits the coarsening of primary particles and improves the mechanical properties of the material, with smaller deformation and stress during lithium removal and insertion; the oxygen vacancies and lithium borate coating constructed on the surface after boric acid treatment can inhibit the release of unstable oxygen, reduce surface side reactions and inhibit phase changes during the material cycle, thereby improving the material cycle stability and reducing voltage attenuation. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the SEM image of the material of Example 4 of the present invention.

[0029] Figure 2 This is the SEM image of the material of Comparative Example 1 of the present invention.

[0030] Figure 3 The cycle curves of the materials of Example 4 and Comparative Example 1 of the present invention at 25° C. and 1C current density within a voltage range of 2.5V-4.4V for 100 cycles.

[0031] Figure 4 The rate performance of the materials of Example 4 and Comparative Example 1 in the voltage range of 2.5V-4.4V at 25°C and different current densities. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0033] Example 1

[0034] (1) manganese sulfate and nickel sulfate are dissolved in deionized water at a molar ratio of manganese to nickel of 0.60:0.40 to prepare a 2 mol / L uniform salt solution, and 5 g of aluminum sulfate is added to each 2 L of the salt solution; 4 mol / L of NaOH solution and 5 mol / L of ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution and ammonia water are pumped into the reactor at a certain liquid inlet speed, and the coprecipitation reaction parameters are controlled. After the coprecipitation reaction for 12 hours, the mixture is washed with deionized water until the pH is neutral, and then dried at 120°C in a forced air drying oven for 12 hours to obtain an Al-containing lithium-rich manganese-based precursor.

[0035] (2) The Al-containing lithium-rich manganese-based hydroxide system precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2, and the precursor and tungsten oxide were uniformly mixed at a mass ratio of 1:0.02 by a three-dimensional mixer at a speed of 30 r / min for 2 hours to obtain a mixture.

[0036] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 3 h, then heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 20 h, and cooling the mixture to room temperature in the furnace to obtain an Al and W co-doped monolithic manganese-rich positive electrode material.

[0037] (4) The sintered positive electrode material obtained in step (3) is mixed uniformly with boric acid in a mass ratio of 1:0.005 by a three-dimensional mixer at a speed of 30 r / min for 2 h, placed in a crucible or a sagger, placed in a sintering furnace, and heated to 500° C. at a heating rate of 5° C. / min for 5 h, and then cooled to room temperature with the furnace to obtain the final product, which is a sintered lithium-rich manganese-based positive electrode material with Al and W co-doping, surface oxygen vacancies, and spinel structure.

[0038] Example 2

[0039] (1) manganese sulfate, nickel sulfate and cobalt sulfate are dissolved in deionized water at a molar ratio of manganese, nickel and cobalt of 0.58:0.40:0.02 to prepare a 2 mol / L uniform salt solution, and 5 g of aluminum sulfate is added to each 2 L of the salt solution; 4 mol / L of NaOH solution and 5 mol / L of ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution and ammonia water are pumped into the reactor at a certain liquid inlet speed, and the coprecipitation reaction parameters are controlled. After the coprecipitation reaction for 12 hours, the mixture is washed with deionized water until the pH is neutral, and then dried at 120°C in a forced air drying oven for 12 hours to obtain an Al-containing lithium-rich manganese-based precursor.

[0040] (2) The Al-containing lithium-rich manganese-based hydroxide system precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2, and the precursor and tungsten oxide were uniformly mixed at a mass ratio of 1:0.02 by a three-dimensional mixer at a speed of 30 r / min for 2 hours to obtain a mixture.

[0041] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 3 h, then heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 20 h, and cooling the mixture to room temperature in the furnace to obtain an Al and W co-doped monolithic manganese-rich positive electrode material.

[0042] (4) The sintered positive electrode material obtained in step (3) is mixed uniformly with boric acid in a mass ratio of 1:0.005 by a three-dimensional mixer at a speed of 30 r / min for 2 h, placed in a crucible or a sagger, placed in a sintering furnace, and heated to 500° C. at a heating rate of 5° C. / min for 5 h, and then cooled to room temperature with the furnace to obtain the final product, which is a sintered lithium-rich manganese-based positive electrode material with Al and W co-doping, surface oxygen vacancies, and spinel structure.

[0043] Example 3

[0044] (1) manganese sulfate, nickel sulfate and cobalt sulfate are dissolved in deionized water at a molar ratio of manganese, nickel and cobalt of 0.58:0.40:0.02 to prepare a 2 mol / L uniform salt solution, and 5 g of aluminum sulfate is added to each 2 L of the salt solution; 4 mol / L of NaOH solution and 5 mol / L of ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution and ammonia water are pumped into the reactor at a certain liquid inlet speed, and the coprecipitation reaction parameters are controlled. After the coprecipitation reaction for 12 hours, the mixture is washed with deionized water until the pH is neutral, and then dried at 120°C in a forced air drying oven for 12 hours to obtain an Al-containing lithium-rich manganese-based precursor.

[0045] (2) The Al-containing lithium-rich manganese-based hydroxide system precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2, and the precursor and tungsten oxide were uniformly mixed at a mass ratio of 1:0.02 by a three-dimensional mixer at a speed of 30 r / min for 2 hours to obtain a mixture.

[0046] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 3 h, then heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 20 h, and cooling the mixture to room temperature in the furnace to obtain an Al and W co-doped monolithic manganese-rich positive electrode material.

[0047] (4) The sintered positive electrode material obtained in step (3) is mixed uniformly with boric acid in a mass ratio of 1:0.010 by a three-dimensional mixer at a speed of 30 r / min for 2 h, placed in a crucible or a sagger, placed in a sintering furnace, and heated to 500° C. at a heating rate of 5° C. / min for 5 h, and then cooled to room temperature with the furnace to obtain the final product, which is a sintered lithium-rich manganese-based positive electrode material with Al and W co-doping, surface oxygen vacancies, and spinel structure.

[0048] Example 4

[0049] (1) manganese sulfate, nickel sulfate and cobalt sulfate are dissolved in deionized water at a molar ratio of manganese, nickel and cobalt of 0.58:0.40:0.02 to prepare a 2 mol / L uniform salt solution, and 5 g of aluminum sulfate is added to each 2 L of the salt solution; 4 mol / L of NaOH solution and 5 mol / L of ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution and ammonia water are pumped into the reactor at a certain liquid inlet speed, and the coprecipitation reaction parameters are controlled. After the coprecipitation reaction for 12 hours, the mixture is washed with deionized water until the pH is neutral, and then dried at 120°C in a forced air drying oven for 12 hours to obtain an Al-containing lithium-rich manganese-based precursor.

[0050] (2) The Al-containing lithium-rich manganese-based hydroxide system precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2, and the precursor and tungsten oxide were uniformly mixed at a mass ratio of 1:0.02 by a three-dimensional mixer at a speed of 30 r / min for 2 hours to obtain a mixture.

[0051] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 3 h, then heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 20 h, and cooling the mixture to room temperature in the furnace to obtain an Al and W co-doped monolithic manganese-rich positive electrode material.

[0052] (4) The sintered positive electrode material obtained in step (3) is mixed uniformly with boric acid in a mass ratio of 1:0.015 by a three-dimensional mixer at a speed of 30 r / min for 2 h, placed in a crucible or a sagger, placed in a sintering furnace, and heated to 500° C. at a heating rate of 5° C. / min for 5 h, and then cooled to room temperature with the furnace to obtain the final product, which is a sintered lithium-rich manganese-based positive electrode material with Al and W co-doping, surface oxygen vacancies, and spinel structure.

[0053] The SEM image of the material prepared in this example is as follows Figure 1 shown.

[0054] Example 5

[0055] (1) manganese sulfate, nickel sulfate and cobalt sulfate are dissolved in deionized water at a molar ratio of manganese, nickel and cobalt of 0.58:0.40:0.02 to prepare a 2 mol / L uniform salt solution, and 5 g of aluminum sulfate is added to each 2 L of the salt solution; 4 mol / L of NaOH solution and 5 mol / L of ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution and ammonia water are pumped into the reactor at a certain liquid inlet speed, and the coprecipitation reaction parameters are controlled. After the coprecipitation reaction for 12 hours, the mixture is washed with deionized water until the pH is neutral, and then dried at 120°C in a forced air drying oven for 12 hours to obtain an Al-containing lithium-rich manganese-based precursor.

[0056] (2) The Al-containing lithium-rich manganese-based hydroxide system precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2, and the precursor and tungsten oxide were uniformly mixed at a mass ratio of 1:0.02 by a three-dimensional mixer at a speed of 30 r / min for 2 hours to obtain a mixture.

[0057] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 3 h, then heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 20 h, and cooling the mixture to room temperature in the furnace to obtain an Al and W co-doped monolithic manganese-rich positive electrode material.

[0058] (4) The sintered positive electrode material obtained in step (3) is mixed uniformly with boric acid in a mass ratio of 1:0.020 by a three-dimensional mixer at a speed of 30 r / min for 2 hours, placed in a crucible or a sagger, placed in a sintering furnace, and heated to 500° C. at a heating rate of 5° C. / min for 5 hours, and then cooled to room temperature with the furnace to obtain the final product, which is a sintered lithium-rich manganese-based positive electrode material with Al and W co-doping, surface oxygen vacancies, and spinel structure.

[0059] Example 6

[0060] (1) manganese sulfate, nickel sulfate and cobalt sulfate are dissolved in deionized water at a molar ratio of manganese, nickel and cobalt of 0.58:0.40:0.02 to prepare a 2 mol / L uniform salt solution, and 5 g of aluminum sulfate is added to each 2 L of the salt solution; 4 mol / L of NaOH solution and 5 mol / L of ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution and ammonia water are pumped into the reactor at a certain liquid inlet speed, and the coprecipitation reaction parameters are controlled. After the coprecipitation reaction for 12 hours, the mixture is washed with deionized water until the pH is neutral, and then dried at 120°C in a forced air drying oven for 12 hours to obtain an Al-containing lithium-rich manganese-based precursor.

[0061] (2) The Al-containing lithium-rich manganese-based hydroxide system precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2, and the precursor and tungsten oxide were uniformly mixed at a mass ratio of 1:0.02 by a three-dimensional mixer at a speed of 30 r / min for 2 hours to obtain a mixture.

[0062] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 3 h, then heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 20 h, and cooling the mixture to room temperature in the furnace to obtain an Al and W co-doped monolithic manganese-rich positive electrode material.

[0063] (4) The sintered positive electrode material obtained in step (3) is mixed uniformly with boric acid in a mass ratio of 1:0.025 by a three-dimensional mixer at a speed of 30 r / min for 2 h, placed in a crucible or a sagger, placed in a sintering furnace, and heated to 500° C. at a heating rate of 5° C. / min for 5 h, and then cooled to room temperature with the furnace to obtain the final product, which is a sintered lithium-rich manganese-based positive electrode material with Al and W co-doping, surface oxygen vacancies, and spinel structure.

[0064] Comparative Example 1

[0065] (1) manganese sulfate, nickel sulfate, and cobalt sulfate are dissolved in deionized water at a molar ratio of manganese, nickel, and cobalt of 0.58:0.40:0.02 to prepare a 2 mol / L uniform salt solution; 4 mol / L NaOH solution and 5 mol / L ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution, and ammonia water are pumped into a reactor at a certain liquid inlet speed, the coprecipitation reaction parameters are controlled, and a lithium-rich manganese-based precursor is obtained after filtering, washing, and drying.

[0066] (2) The obtained lithium-rich manganese-based precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2 by a three-dimensional mixer at a speed of 30 r / min for 2 h to obtain a mixture.

[0067] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 500° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 5 h, then heating the temperature to 850° C. at a heating rate of 5° C. / min and keeping the temperature for 12 h, and cooling the mixture to room temperature to obtain a lithium-rich manganese-based positive electrode material without any doping elements and surface treatment.

[0068] The SEM image of the material prepared in this comparative example is as follows Figure 2 The cycle curves of Example 4 and the comparative example materials at 25°C and 1C current density within the voltage range of 2.5V-4.4V for 100 cycles are shown in FIG. Figure 3 The rate performance of Example 4 and the comparative example materials at 25°C and different current densities in the voltage range of 2.5V-4.4V is shown as follows: Figure 4 shown.

[0069] Comparative Example 2

[0070] (1) Manganese sulfate, nickel sulfate and cobalt sulfate are dissolved in deionized water at a molar ratio of manganese, nickel and cobalt of 0.58:0.40:0.02 to prepare a 2 mol / L uniform salt solution, and 5 g of aluminum sulfate is added to each 2 L of the salt solution; 4 mol / L of NaOH solution and 5 mol / L of ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution and ammonia water are pumped into the reactor at a certain liquid inlet speed, and the coprecipitation reaction parameters are controlled. After the coprecipitation reaction for 12 hours, the mixture is washed with deionized water until the pH is neutral, and then dried at 120°C in a forced air drying oven for 12 hours to obtain an Al-containing lithium-rich manganese-based precursor.

[0071] (2) The Al-containing lithium-rich manganese-based hydroxide system precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2 by a three-dimensional mixer at a speed of 30 r / min for 2 h to obtain a mixture.

[0072] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 3 h, then heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 20 h, and cooling the mixture to room temperature in the furnace to obtain an Al-doped monosintered lithium-rich manganese-based positive electrode material.

[0073] Comparative Example 3

[0074] (1) Manganese sulfate, nickel sulfate and cobalt sulfate are dissolved in deionized water at a molar ratio of manganese, nickel and cobalt of 0.58:0.40:0.02 to prepare a 2 mol / L uniform salt solution, and 5 g of aluminum sulfate is added to each 2 L of the salt solution; 4 mol / L of NaOH solution and 5 mol / L of ammonia water are prepared; under the protection of N2, the metal salt solution, NaOH solution and ammonia water are pumped into the reactor at a certain liquid inlet speed, and the coprecipitation reaction parameters are controlled. After the coprecipitation reaction for 12 hours, the mixture is washed with deionized water until the pH is neutral, and then dried at 120°C in a forced air drying oven for 12 hours to obtain an Al-containing lithium-rich manganese-based precursor.

[0075] (2) The Al-containing lithium-rich manganese-based hydroxide system precursor and lithium carbonate were uniformly mixed at a molar ratio of 1:1.2, and the precursor and tungsten oxide were uniformly mixed at a mass ratio of 1:0.02 by a three-dimensional mixer at a speed of 30 r / min for 2 hours to obtain a mixture.

[0076] (3) placing the mixture obtained in step (2) in a crucible or a sagger, placing it in a sintering furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min in an air atmosphere and keeping the temperature for 3 h, then heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 20 h, and cooling the mixture to room temperature in the furnace to obtain an Al and W co-doped monolithic manganese-rich positive electrode material.

[0077] Table 1 Electrochemical properties of materials

[0078]

[0079] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a synergistically modified lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: A co-precipitation method is used to synthesize an Al-containing lithium-rich manganese-based hydroxide system precursor, which is uniformly mixed with a lithium source and a W source in a certain amount, and then sintered in an air atmosphere to obtain an Al- and W-co-doped lithium-rich manganese-based positive electrode material; the obtained positive electrode material is uniformly mixed with a B source in a certain mass ratio, and secondary sintered, and naturally cooled to room temperature to obtain a synergistically modified lithium-rich manganese-based positive electrode material; The steps include: (1) mixing a nickel source, a manganese source, a cobalt source and an Al source in deionized water to obtain a transition metal source solution, adding a complexing agent and a precipitant to the transition metal source solution to perform nucleation and growth of particles, and filtering, washing and drying to obtain a lithium-rich manganese-based precursor; (2) mixing the lithium-rich manganese-based precursor, the lithium source and the W source in step (1) to obtain a mixture; (3) performing a first sintering on the mixture of step (2) to obtain a sintered positive electrode material; (4) After mixing the first sintered positive electrode material in step (3) with the B source, a second sintering is performed to obtain the synergistically modified lithium-rich manganese-based positive electrode material.

2. The synergistically modified lithium-rich manganese-based positive electrode material and its preparation method and application according to claim 1, characterized in that: The nickel source in step (1) includes any one of nickel sulfate, nickel nitrate or nickel acetate or a combination of at least two thereof, the manganese source includes any one of manganese sulfate, manganese nitrate or manganese acetate or a combination of at least two thereof, the cobalt source includes any one of cobalt sulfate, cobalt nitrate or cobalt acetate or a combination of at least two thereof, the Al source includes any one of aluminum sulfate, aluminum nitrate, aluminum acetate or aluminum oxide or a combination of at least two thereof, the molar ratio of nickel, manganese and cobalt in the nickel source, manganese source and cobalt source is (0.1-0.5):(0.5-0.9):(0-0.5), and the molar sum of nickel, manganese and cobalt is 1.

3. The method for preparing the synergistically modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The introduction ratio of the Al source in the transition metal source solution in step (1) is 0.1-50 g / L, and the total concentration of nickel, manganese and cobalt corresponding to the nickel source, manganese source and cobalt source in the transition metal source solution is 1-4 mol / L; the precipitant in step (1) is sodium hydroxide, and the precipitant is pumped in at a concentration of 1-6 mol / L; the complexing agent in step (1) includes any one of ammonia water, sodium tartrate or citric acid or a combination of at least two thereof, and the complexing agent is dropwise pumped in at a concentration of 0.5-10 mol / L.

4. The method for preparing the synergistically modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (1), the particle nucleation and growth process is carried out at a temperature of 30-60° C., a pH value of 9-12, a stirring speed of 600-1400 rpm, and a liquid feeding speed of 20-700 mL / h, so that the particle size D50 of the lithium-rich manganese-based precursor is 2-12 μm.

5. The method for preparing the synergistically modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The molar ratio of the precursor to the lithium source in step (2) is 1:(0.9-2.0), and the lithium source includes any one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium manganate, lithium sulfide, lithium chloride, lithium sulfate, lithium iodide, lithium bromide or lithium peroxide, or a combination of at least two of them; the mass ratio of the lithium-rich manganese-based precursor to the W source in step (2) is 1:(0.001-0.5), and the W source includes any one of tungsten oxide, sodium tungstate, ammonium tungstate, calcium tungstate, cobalt tungstate, ferrous tungstate or zinc tungstate, or a combination of at least two of them.

6. The method for preparing the synergistically modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: Step (3) The atmosphere of the first sintering is an air atmosphere, and the first sintering includes a first-stage sintering and a second-stage sintering performed in sequence, the heating rate of the first-stage sintering is 1-10°C / min, the first-stage sintering is heated to 150-650°C, and then the insulation time is 0-10h, the heating rate of the second-stage sintering is 1-10°C / min, the second-stage sintering is heated to 650-1100°C, and then the insulation time is 5-24h, and the second-stage sintering is cooled to room temperature to obtain the first-stage sintered positive electrode material.

7. The method for preparing the synergistically modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (4), the mass ratio of the fired positive electrode material to the B source is 1:(0.001-0.5), and the B source includes any one of boric acid, borate, boron trioxide, cobalt boride or molybdenum boride, or a combination of at least two thereof.

8. The method for preparing the synergistically modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (4), the sintered positive electrode material is mixed evenly with the B source, placed in a crucible or a sagger, placed in a sintering furnace, heated to 200°C-800°C at a heating rate of 1-10°C / min and kept warm for 1-12 hours, and then cooled to room temperature with the furnace to obtain the synergistically modified lithium-rich manganese-based positive electrode material.

9. A lithium-rich manganese-based positive electrode material prepared according to the method according to any one of claims 1 to 8.

10. Application of the lithium-rich manganese-based positive electrode material prepared by the method according to any one of claims 1 to 8 in the field of lithium-ion batteries.

Citation Information

Patent Citations

  • Ternary positive electrode material, preparation method thereof and lithium ion battery

    CN115893521A

  • Lithium-rich manganese-based positive electrode material with high cycle stability, preparation method and lithium battery

    CN116190635A

  • Lithium-rich manganese positive electrode material as well as preparation method and application thereof

    CN116417604A

  • High-nickel precursor, positive electrode material and preparation methods of high-nickel precursor and positive electrode material

    CN116425210A

  • Ternary precursor of doped metal element, and manufacturing method therefor and application thereof

    WO2023005030A1